Enhancing student engagement through a gallery walk: applying multiple strategies to communicate scientific concepts - Watumesa Agustina Tan; Sarah Perrault (Journal of Microbiology & Biology Education)
ABSTRACT Effective science communication skills are essential for scientists across sectors to engage with non-specialist audiences. This paper describes a gallery walk activity designed to help science students learn and practice strategies for making complex scientific concepts accessible to diverse audiences. The activity was implemented in a Science Communication course with 24 students from the Biotechnology and Food Technology programs. It introduces students to a range of rhetorical strategies, such as etymology, analogy, and personal storytelling, which are applied in exercises that encourage students to communicate scientific topics in engaging and relevant ways. The gallery walk encourages students to interact with eight stations, each focused on a specific communication strategy. By generating examples and discussing varied approaches, students may gain insights into adapting their communication for different contexts and audiences. The activity is a flexible and engaging approach to teaching science communication that may foster critical thinking and build students' confidence in applying communication techniques. Its adaptable format makes the gallery walk suitable for various classroom settings, supporting both large and small class sizes.